Problems and perspectives of Croatian cinema : interview analysis - Dunatov, Dario (Array, 2019)
Contemporary social trends such as globalization and technological develop- ment affect national cinema as well as world cinema in general. Discussions about national cinema should therefore be placed within the context of the nation-state itself and transnationally. The continuity of fi lm industry in Croatia exists from the very beginnings of the fi lm, but it as a product of the cinema that is closely related to social, political and economic circumstances which had multiple implications on its development. The aim of the paper was to examine the features of Croatian national cinema as well as the aspects of its affi rmation and reception, which ultimately enabled understanding of the developmental and integrative factors of Croatian cinema. Insight into the developmental and integrative factors of Croatian cinema presents a wider picture of the problems and perspectives of Croatian national cinema today. The qualitative approach was used in the research and semistructured interviews were conducted with interviewees closely related to film and film production. The analysis shows diffi culties in developing a specifi c style and achieving greater international visibility. An important moment was the establishment of Croatian Audiovisual Centre which devised a plan for Croatian national cinema and brought fi nancial independence. This consequently led to the rise of investments and quality of fi lms and even to international festival visibility of Croatian cinema. At the beginning of the 21st century Croatian fi lm industry developed infrastructure, provided support for young fi lmmakers and created the preconditions for quality and innovative fi lm titles.